Evaluation and comparison of diabetic and non-diabetic patients infected by COVID-19 and phenotypes of severity: an analytical and cross-sectional study in a reference hospital of the Federal District, Brazil (Research, Society and Development, 2021)
Introduction: In March 2020 the World Health Organization (WHO) declared a pandemic for the disease called COVID 19, caused by a new acute severe coronavirus respiratory syndrome 2 (SARS-CoV-2), being a public health emergency of international interest. Since the beginning of the pandemic, diabetes mellitus has emerged as a complicating factor, with unfavorable outcomes compared to the non-diabetic population. Thus, our study aimed to evaluate and compare, through an analytical, cross-sectional and descriptive study, the phenotypes of severity among people with diabetic and non-diabetic COVID-19 in a reference hospital in the Federal District, Brazil. Material and methods: Through an active search of data in the medical records of hospitalized patients diagnosed with COVID-19 by the"Real Time Polymerase Chain Reaction" (RT-PCR) method, 2041 individuals who, after exclusion criteria, selected a total of 762 for the proposed study were selected, comparing clinical and laboratory data between the group with diabetes and without diabetes. Descriptive statistics were performed with mean and standard deviation values, absolute frequency and relative percentage. The normality and homogeneity of the data were calculated with the Shapiro-Wilk and Levene test, respectively. The student's t-test for independent samples was used to compare the continuous variables and the chi-square test was used to compare categorical variables between diabetic and non-diabetic patients. Findings: Individuals with diabetes presented a more severe clinical picture when compared to those without the disease. Evidencing an independent risk factor for a worse prognosis. Discussion: our findings are in line with other studies already conducted, showing that the chronic inflammatory component of the disease seems to be the main trigger for unfavorable outcomes. Conclusion: Considering the epidemiological importance of diabetes, urgent research is made that elucidate the above-mentioned doubts, aiming at more appropriate therapeutic interventions and, therefore, improving outcomes in this population. In the case of a new and still little known disease, with several questions, probably many of the answers will only come over time, through more robust, prospective and randomized studies, with larger and more diverse populations.